MEDIA DAN PENCITRAAN PEREMPUAN - Nurdin Abd Halim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
This article discusses how is the woman image in mass media and what alternative can be done to make the woman image becomes good.Of analysis can be concluded that the mass media develops the image of woman through the streotype of woman. As a result, woman always becomes the source of media commercialisation and the news concerning woman tends to be discriminative. At the online media, woman is the active consumer in comparison with man so that woman can exposed her social activity. The gender mainstreaming and woman national commission’s program represents strategic resolving alternative to less the discrimination to woman in mass media. So that, to be its execution can be measured and succeed to reach the target, the activity shall be controlled by the independent institution and the government.